2020
DOI: 10.1038/s41467-020-15130-1
|View full text |Cite
|
Sign up to set email alerts
|

Massive and massless charge carriers in an epitaxially strained alkali metal quantum well on graphene

Abstract: We show that Cs intercalated bilayer graphene acts as a substrate for the growth of a strained Cs film hosting quantum well states with high electronic quality. The Cs film grows in an fcc phase with a substantially reduced lattice constant of 4.9 Å corresponding to a compressive strain of 11% compared to bulk Cs. We investigate its electronic structure using angle-resolved photoemission spectroscopy and show the coexistence of massless Dirac and massive Schrödinger charge carriers in two dimensions. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Massive and massless charge carriers were observed on caesium-doped graphene; a system modelled as a strained quantum well [154]. Extended flat bands were reported for this system in a later work [155].…”
Section: Adatom-induced Graphene Superlatticesmentioning
confidence: 76%
See 1 more Smart Citation
“…Massive and massless charge carriers were observed on caesium-doped graphene; a system modelled as a strained quantum well [154]. Extended flat bands were reported for this system in a later work [155].…”
Section: Adatom-induced Graphene Superlatticesmentioning
confidence: 76%
“…A proposal by Ghazaryan et al [356] pointed out a general mechanism for superconductivity induced by an annular Fermi surface. Remarkably, an annular Fermi surface has not only been observed in ABC-trilayer graphene, but in other graphene superlattices [154] as well.…”
Section: Correlated Physics In Triple-layer Graphenementioning
confidence: 95%
“…We note that a recent study reported that single-crystalline fcc Cs thin films are stabilized on Cs-intercalated bilayer graphene due to the adhesion energy between Cs and the bilayer graphene substrate. [46] However, in this heterostructure, only 3 ML Cs film has been obtained experimentally so far. [46] In contrast, we have successfully controlled the film thickness up to at least 30 MLs (Figure 3).…”
Section: Evaluation Of Many-body Interactionsmentioning
confidence: 97%
“…Intercalation of foreign guest species in transition metal dichalcogenides (TMDs), such as MoS 2 , WS 2 , MoSe 2 , WSe 2 , et al, is beginning to attract considerable interest. This is in part due to the novel electronic properties of these systems enabling prospective applications to high-performance electronics, optoelectronics, electrochemical catalysis, energy storage and conversion (such as ionic batteries), and biological systems. In this context, studies of intercalation specifically for MoS 2 have attracted considerable attention. , On the other hand, TMD nanosheets are often fabricated by intercalation, and various methods toward this goal have been utilized. , Also, there do already exist extensive studies of near-surface intercalation in other types of layered van der Waals (vdW) materials, including graphite (or multilayer graphene) and SiC- , or metal-supported graphene layers. The above studies generally involve homogeneously distributed intercalant atoms in the TMD interlayer spaces.…”
mentioning
confidence: 99%
“…8,9 On the other hand, TMD nanosheets are often fabricated by intercalation, and various methods toward this goal have been utilized. 10,11 Also, there do already exist extensive studies of near-surface intercalation in other types of layered van der Waals (vdW) materials, including graphite (or multilayer graphene) 12 and SiC- 13,14 or metal-supported 15 graphene layers. The above studies 1−11 generally involve homogeneously distributed intercalant atoms in the TMD interlayer spaces.…”
mentioning
confidence: 99%